Rúbricas para el fortalecimiento del desempeño docente - Cárdenas-Valverde, Juan (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The research began with the question: What is the influence of the rubric in the development of the teaching performance of teachers in the province of Huancayo (Peru)? The objective was: To determine the influence of the rubric in the development of the teaching performance of teachers in the province of Huancayo. The hypothesis was: The application of the rubric has a positive influence on the development of the teaching performance of teachers in the province of Huancayo. The research was of an applicative type, since the rubric for the development of teaching performance was applied. The methods were: scientific, descriptive, experimental and statistical. The research design was single group only after. The population was made up of teachers from educational institutions in the province of Huancayo and the sample, by some teachers from these institutions. The data collection techniques used were: observation, survey and recording. In data processing and analysis techniques, the following were obtained: descriptive and inferential statistics. The conclusion is: The application of the rubric has a positive influence on the development of the teaching performance of teachers in the province of Huancayo.